Nanobubble technology enhanced ozonation process for ammonia removal - Wu, Yuncheng; Tian, Wei; Zhang, Yang; Fan, Wei; Liu, Fang; Zhao, Jiayin; Wang, Mengmeng; Liu, Yu; Lyu, Tao (MDPI, 2022)
Ozone (O3) has been widely used for water and wastewater treatment due to its strong oxidation ability, however, the utilization efficiency of O3 is constrained by its low solubility and short half-life during the treatment process. Thereby, an integrated approach using novel nanobubble technology and ozone oxidation method was studied in order to enhance the ozonization of ammonia. Artificial wastewater (AW) with an initial concentration of 1600 mg/L ammonia was used in this study. In the ozone-nanobubble treatment group, the concentration of nano-sized bubbles was 2.2 × 107 particles/mL, and the bubbles with <200 nm diameter were 14 times higher than those in the ozone-macrobubble treatment control group. Ozone aeration was operated for 5 min in both nanobubble treatment and control groups, however, the sampling and measurement were conducted for 30 min to compare the utilization of O3 for ammonia oxidation. H+ was the by-product of the ammonia ozonation process, thus the pH decreased from 8 to 7 and 7.5 in nanobubble treatment and control groups, respectively, after 30 min of operation. The fast removal of ammonia was observed in both systems in the first 10 min, where the concentration of ammonia decreased from 1600 mg/L to 835 and 1110 mg/L in nanobubble treatment and control groups, respectively. In the nanobubble treatment group, ammonia concentrations kept the fast-decreasing trend and reached the final removal performance of 82.5% at the end of the experiment, which was significantly higher than that (44.2%) in the control group. Moreover, the first-order kinetic model could be used to describe the removal processes and revealed a significantly higher kinetic rate constant (0.064 min−1) compared with that (0.017 min−1) in the control group. With these results, our study highlights the viability of the proposed integrated approach to enhance the ozonation of a high level of ammonia in contaminated water.
Keywords: advanced oxidation process; ammonia oxidation; nanobubbles; water and wastewater treatment